Evaluasi Pembelajaran PAI Menggunakan Model Context, Input, Process, dan Product (CIPP) di Kelas XI SMA Negeri 1 Garut - Meydita Dwi Putri; Masripah Masripah; Iman Saifullah (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study aims to evaluate the implementation of Islamic Religious Education (PAI) learning in Grade XI at SMA Negeri 1 Garut using the CIPP evaluation model (Context, Input, Process, Product). The background of this research is based on the importance of evaluating PAI learning not only in terms of cognitive achievement but also in affective and religious behavioral aspects of students. This study employs a qualitative approach with data collection techniques including interviews, observations, and documentation, which are analyzed descriptively according to the four components of the CIPP model. The results show that in the context aspect, PAI learning has been aligned with the Merdeka Curriculum, the school’s vision, and is supported by a conducive religious culture. In the input aspect, teacher readiness, learning tools, and facilities are considered adequate. In the process aspect, learning activities are generally effective with varied teaching methods and active student participation. In the product aspect, students demonstrate good academic achievement as well as improvements in religious attitudes and positive behavioral changes, although the internalization of religious values is not evenly distributed among all students. Overall, PAI learning has been implemented well, but it still requires strengthened innovation and continuous guidance.